AN ANALYSIS OF THE EFFECTIVENESS OF ELECTRONIC MEDIA FOR READING COMPREHENSION: EFL STUDENTS' PERSPECTIVES - Nelson Frits Manalaksak Lumban Tobing; Lulud Oktaviani (Faculty of Arts and Education, 2022)
The advancement of technology has given an impact on education, especially in comprehension way. This means in the world of literature, especially reading people get the benefit of improving their capability in terms of comprehension everywhere and anywhere. Comprehension has given the best impact to develop skills like listening, speaking, and reading. The main focus of this will be reading comprehension with the tools of technology advancement. This is leading to a better quality of learning for the people, especially the EFL students and language learners. There are so many media that allow the reader to access the easiest way to gain information or to develop themselves. Especially in the era of 4.0 where technology became the main media for the people to reach. This is important to give an analysis of the effectiveness of electronic media for the readers in this era. The effectivity allowed the reader to gain easy access, to the improvement and any other kind.